Building location-based service with Java technologies - Devaraju, Anusuriya; Beddus, Simon (2005)
The growing use of Java in Location-based Service provides an opportunity to find solutions for problems and challenges in the rapidly changing telecommunications environment. This paper describes the development of location-based service components using Java technologies. The technologies include J2ME, Servlet, Java Server Pages (JSP) and XML Java Binding Tool. The developed components are the location server simulator, location service application and device client application. This study is crucial for support of BT’s launch of User Location Service on prototype ERICA mobile application platform through supporting the testing and validation of the platform components.